Cholesterol of Low-Density Lipoprotein-Containing Circulating Immune Complexes Improves Prognosis of Asymptomatic Carotid Atherosclerosis - A. N. Orekhov; N. A. Orekhov; A. V. Omelchenko; I. A. Sobenin (Фундаментальная и клиническая медицина, 2024)
Aim. Previously, low-density lipoprotein-containing circulating immune complexes (LDL-CIC) were found in the blood of atherosclerotic patients. High diagnostic and prognostic significance of cholesterol level in LDL-CIC (Chol-CIC) in relation to the development of asymptomatic atherosclerosis suggested its clinical utility. Here we attempted to improve the prognostic value of CholCIC by combining this marker with other features.Materials and Methods. The study included 101 male patients with asymptomatic carotid atherosclerosis. During 1 year, we carried out quarterly measurements of clinical and biochemical features including Chol-CIC and intima-media thickness (IMT).Results. Combination with age increased the prognostic significance of Chol-CIC from 63.5% to 78.3% that exceeded those of low-density lipoprotein cholesterol (LDL-C) and Chol-CIC alone. Age did not improve prognostic significance of other lipid parameters. Therefore, Chol-CIC had higher prognostic significance in comparison to other lipid profile parameters.Conclusion. Combination of Chol-CIC and patient age may be used for the prognosis of increasing intima-media thickness.